A Fundação Rockefeller e a formação de quadros para a enfermagem (Brasil: 1917-1951) - Ana Paula Korndörfer (Centre de Recherches sur les Mondes Américains, 2019)
At the global level, the Rockefeller Foundation (RF), an American philanthropic institution, had an important role in the granting of fellowships for medical science and public health. Our proposal in this text is to discuss, mainly using the prosopographic method, the Foundation's role in the training of cadres for Brazilian public health, and especially for nursing. From information available in the directory of fellowship holders of the institution, we know that, between 1917 and 1951, 28 professionals residing in Brazil received 31 fellowships to carry out studies in the nursing area. The analysis focuses on these 28 fellowship holders, highlighting the process of their selection by the US institution and their social profile, as well as the training they received. It is assumed that the objective of granting fellowships was to train people to act in strategic positions in official health agencies or as directors and/or teachers in hygiene, public health and/or nursing schools in the countries of origin and, in this way, to determine institutional orientations and priorities, reflecting some of the ideas and practices supported and valued by the Rockefeller Foundation and with which they had become acquainted during the period of studies.